EFEKTIFITAS REWARD DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SDN 06 ANDALEH BARUH BUKIK - Handayani, Putri; Dayu, Refni; Andriani, Wahyu (JISPE Journal of Islamic Primary Education, 2023)
This research method is a quantitative method using experimental types, while this research approach is a pre-experimental design type one group pretest-postest. The research sample was obtained through a saturated sample technique or total sampling where all populations were sampled, namely all class V students totaling 25 people. Data collection uses essay test questions and questionnaires with statistical data analysis techniques with t-tests. From the final test result data, it shows that the final average score of students in the pretest is 44.6 with a percentage of completeness of 20% and postest which is 86.04 with a percentage of completeness of 88%. the results of student learning motivation scores on the questionnaire test at SDN 06 Andaleh Baruh Bukik were 25 students with a total score of 2206 and an average score of 88.24. It can be concluded that students' learning motivation is in a very high category. In this study, a hypothesis test was also carried out with a posttest pretest t-test with an SPSS application of 0.000<0.005, then H0 was rejected and Ha was accepted so that a decision could be made that giving rewards was effective in increasing the learning motivation of grade V students in mathematics subjects at SDN 06 Andaleh Baruh Bukik.